Plasma Calcium and Phosphorus Levels and Cardiovascular Disease Risks in Egyptian Type 2 Diabetic Patients - Al-Okbi, Sahar; Sabry, Seham; Al-Siedy, Enas S. K.; Elsayed, Shaimaa (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Cardiovascular complication of diabetes is considered an important issue that needs deep investigations. The levels of plasma calcium (Ca) and phosphorus (P) have been implicated as having an association to cardiovascular diseases. AIM: The objective of the present research was to study the plasma levels of both Ca and P and their association to the atherogenic ratio; total cholesterol: high density lipoprotein-cholesterol and the plasma albumin in male and female patients with type 2-diabetes. The interrelation between anthropometric parameters represented by body mass index (BMI), waist circumference and waist/hip ratio with Ca and P were studied. Also, the association between plasma Ca and P with their dietary intake were investigated. Subjects and METODS: Thirty-one type 2-diabetic male and female patients participated in the study, in addition of ten healthy subjects. Biochemical parameters, anthropometric measurements and nutrients′ intake were assessed. Biochemical parameters include plasma Ca, P, lipid profile, albumin, liver function tests and creatinine. RESULTS: Plasma Ca levels of female patients of BMI> 30 kg/m2 demonstrated significant increase compared to the control group. All male and female patients showed significant increase in plasma P compared to the control group. Glycosylated hemoglobin of male and females showed significant high values compared to the control group except for diabetic male of BMI>30 kg/m2 that showed insignificant increase. No significant changes in plasma TG and LDL-C levels were noticed compared to the control. Plasma TC of patients showed significant high levels compared to the control group. The levels of HDL-C of patients were significantly lower than that of the control. The ratios of TC/HDL-C diabetic patients either male or female and whatever their BMI were significantly higher than that of the control. No significant changes in plasma activities of ALT and AST and bilirubin levels were observed among the different groups including the control. Plasma albumin levels demonstrated significant reduction compared to the control group whatever their sexes or BMI. Plasma creatinine levels of the different diabetic groups showed insignificant change from the control group except for the male group of BMI<30 kg/m2 that showed significant elevation. In male, plasma Ca showed significant negative correlation with albumin and positive correlation with creatinine and dietary vitamin D. In female, a significant positive correlation was noticed between plasma and dietary P while a negative correlation was observed between plasma Ca and dietary iron. CONCLUSION: Elevated of plasma P together with reduced plasma albumin and elevated TC/HDL-C may reflect an association of plasma P to CVD in male and female diabetic subjects while high plasma Ca might predict CVD in only female diabetic patients of BMI > 30 kg/m2.